Integração entre atividades computacionais e experimentais como estratégia pedagógica no estudo de circuitos elétricos no ensino médio - Maia, Glauco Denes Galvão (2015)
This research aims to investigate how the realization of computational and experimental activities contribute to the development of the learning process. The proposal is to work with activities that can show that it is possible to learn electrical circuits using the integration of Multisim software with experimental practices. The work is based on the Theory of Conceptual Fields, established by Gérard Vergnaud, as a theoretical framework, because it is a theory that best presents elements for analysis of the subjectin-action, the focus of our investigation. For this author, knowledge is organized into conceptual fields whose domain on the part of the learner, is happening over a long period of time, through experience, maturity and learning (MOREIRA, 2002). It is planned and applied an educational sequence, educational product, targeted to meet the characteristics of this research. The application of the sequence took place in a state school in the city of Manaus - AM, with a 3rd year high school class. The content of electrical circuits was worked using Multisim software, considered free, concomitant to the experimental practice in order to make them mutually. In all activities, instruments of data collection were used such as: responses and subjective reports of the students in the scripts of computational and experimental activities; in pre-test and post-test; in the evaluation questionnaires of teaching tools and in the evaluation questionnaire of pedagogical practice. The results show that the proposed integration between activities using Multisim and the experimental practices can provide students a better insight into the epistemological theoretical models in physics, promoting interactivity and their engagement in their own learning, transforming the classroom into an enabling environment for learning.